(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
The pollen morphology of six species of Scabiosa L. (Caprifoliaceae) from Iran has been examined by scanning electron microscopy (SEM). Pollen grains were tricolpate in S. columbaria and triporate in the rest studied species. Two types of exine ornamentation were revealed: spinulate and gemmate. The pollen shape in polar view varied from triangular to circular among investigated taxa. Statistical analysis showed that some quantitative morphological features such as polar axis (P), equatorial axis (E) and aperture diameter were main characters in identification of the taxa studied. These taxa were separated from each other using cluster analysis and placed within two clusters. Our result based on UPGMA analysis is in agreement with morphological classification and recent findings on taxonomic position of the Scabiosa. Bangladesh J. Plant Taxon. 23(2): 215-222, 2016 (December)